Efficacy of Cardiopulmonary Resuscitation in the Supine Position With Manual Displacement of the Uterus Versus Lateral Tilt Using a Firm Wedge. Issue 3 (September 2015) - Butcher, M.; Ip, J.; Bushby, D.; Yentis, S.M.
<x xml:space="preserve">Abstract</x> (Anaesthesia. 2014;69(8):868–871)